2015
DOI: 10.1007/978-3-319-13494-9
|View full text |Cite
|
Sign up to set email alerts
|

Limnoperna Fortunei

Abstract: Biological Invasions represent one of those rare themes that cut across the disciplines of academic biology, while having profound environmental, philosophical, socioeconomic, and legislative implications at a global scale. There can be no doubt that biological invasions represent the single greatest threat to biodiversity past the activities of humankind itself. The implications are far reaching. Novel ecological and evolutionary forces are now directing the future expression of life itself, as native species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 14 publications
0
4
0
6
Order By: Relevance
“…However, the dissolved oxygen has been found as a factor that regulates the reproductive activity and survival of the golden mussel, impeding its uncontrolled proliferation (Oliveira et al, 2010bEilers et al, 2011;Bonel et al, 2013), limiting the abundance increase, but not interfering in the establishment of the species (Oliveira et al, 2010b). Perepelizin & Boltovskoy (2015) consider that oxygen deprivation may be a viable alternative for the control of mussel fouling in industrial installations, because they observed total mortality at dissolved oxygen levels < 0.16 mg/Lafter 10-12 days (at 27 °C), in addition to higher mortality of smaller mussels (7mm) when oxygen deprivation occurs in lower temperature (at 20 °C). The data presented in our study, show that during the dry season, the lowest percentage of oxygen in shallow lakes, also acts as controller for population L. fortunei, associated with other covariates factors, as water temperature, typically high in the Paraguay River (occasional cold fronts 19.4 to 26.1°C).…”
Section: Discussionmentioning
confidence: 99%
“…However, the dissolved oxygen has been found as a factor that regulates the reproductive activity and survival of the golden mussel, impeding its uncontrolled proliferation (Oliveira et al, 2010bEilers et al, 2011;Bonel et al, 2013), limiting the abundance increase, but not interfering in the establishment of the species (Oliveira et al, 2010b). Perepelizin & Boltovskoy (2015) consider that oxygen deprivation may be a viable alternative for the control of mussel fouling in industrial installations, because they observed total mortality at dissolved oxygen levels < 0.16 mg/Lafter 10-12 days (at 27 °C), in addition to higher mortality of smaller mussels (7mm) when oxygen deprivation occurs in lower temperature (at 20 °C). The data presented in our study, show that during the dry season, the lowest percentage of oxygen in shallow lakes, also acts as controller for population L. fortunei, associated with other covariates factors, as water temperature, typically high in the Paraguay River (occasional cold fronts 19.4 to 26.1°C).…”
Section: Discussionmentioning
confidence: 99%
“…Este tamaño de organismo no presenta barreras físicas en los diferentes sistemas de conducción hidráulica debido a que la mayoría de los sistemas de captación consideran sistemas de filtración o rejas con tamaños de poro mayores a 1000µm. De esta manera, las larvas y estadios con estructuras de fijación (filamentos bisales) ingresan, se asientan y desarrollan colonias bentónicas en el interior de los sistemas de conducción hidráulica, o en diferentes estructuras humanas (Darrigran, 2002;Darrigran, et al, 2007;Boltovskoy, 2015). Las colonias bentónicas asentadas ocasionan macrofouling, afectando los servicios ecosistémicos de los recursos hídricos de la cuenca del Plata (Brugnoli, et al, 2006;Darrigran, et al, 2007;Boltovskoy y Correa 2015).…”
Section: Introductionunclassified
“…Specifically, intensive filter feeders such as bivalves have been shown to influence trophic transfer (Gergs et al, 2011;Nalepa et al, 1998), contribute to decreased primary production (Boltovskoy and Correa, 2014), and restructure food webs (Boltovskoy et al, 2015;Eby et al, 2005) within coastal marine (Alpine and Cloern, 1992), inland river (Sylvester et al, 2005;Vaughn and Hakenkamp, 2001), and large and small lake systems (Beaver et al, 1991). Specifically, intensive filter feeders such as bivalves have been shown to influence trophic transfer (Gergs et al, 2011;Nalepa et al, 1998), contribute to decreased primary production (Boltovskoy and Correa, 2014), and restructure food webs (Boltovskoy et al, 2015;Eby et al, 2005) within coastal marine (Alpine and Cloern, 1992), inland river (Sylvester et al, 2005;Vaughn and Hakenkamp, 2001), and large and small lake systems (Beaver et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of invasive species can also interrupt nutrient dynamics and trophic pathways in aquatic ecosystems. Specifically, intensive filter feeders such as bivalves have been shown to influence trophic transfer (Gergs et al, 2011;Nalepa et al, 1998), contribute to decreased primary production (Boltovskoy and Correa, 2014), and restructure food webs (Boltovskoy et al, 2015;Eby et al, 2005) within coastal marine (Alpine and Cloern, 1992), inland river (Sylvester et al, 2005;Vaughn and Hakenkamp, 2001), and large and small lake systems (Beaver et al, 1991).…”
Section: Introductionmentioning
confidence: 99%